2008
DOI: 10.5194/angeo-26-4023-2008
|View full text |Cite
|
Sign up to set email alerts
|

Tailward propagation of Pi2 waves in the Earth's magnetotail lobe

Abstract: Abstract. Pi2 waves are an intergral part of the substorm process and have been observed on the ground and in space. Using the special ability of Cluster to determine the propagation direction of signals measured in the magnetometer data, it is found that in the lobes of the Earth's magnetotail, for the cases in this study, the Pi2 waves are travelling tailward. The polarization of the waves in the lobes corresponds well with the polarization observed in the highest latitude ground station. The propagation vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…At the same time, these large waves are accompanied by smaller Pi2-like pulsations, often in the form of standing Alfvén waves in the tail lobe, which are one-to-one correlated with pulsations in the polar cap (Keiling et al 2005). We also note the study by Volwerk et al (2008) who reported Pi2-like oscillations in the tail lobe that traveled tailward, which are consistent with this propagation path, if they are interpreted as waves reflected off the ionosphere.…”
Section: Observationssupporting
confidence: 78%
“…At the same time, these large waves are accompanied by smaller Pi2-like pulsations, often in the form of standing Alfvén waves in the tail lobe, which are one-to-one correlated with pulsations in the polar cap (Keiling et al 2005). We also note the study by Volwerk et al (2008) who reported Pi2-like oscillations in the tail lobe that traveled tailward, which are consistent with this propagation path, if they are interpreted as waves reflected off the ionosphere.…”
Section: Observationssupporting
confidence: 78%
“…The overall spectrum becomes rather broadband during the local CD, suggesting the possibility of plasma instabilities with different spatiotemporal characteristic as well as distinct frequency bands, e.g., ballooning (mainly Pi2), the TCS mode (Pi1), and the CCI (above and possibly overlap with the upper edge of the Pi1). During this most active period of substorms there are also other viable mechanisms generating Pi1/Pi2 waves (e.g., Holter et al, 1995;Volwerk et al, 2008). Those instability/wave processes may coexist and cooperate, driving the current sheet into a turbulence state (Lui, 2002;Cheng, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In order to better show the wave power and polarization characteristics of the Pc2 waves observed by Cluster 3, a wavelet analysis is used to obtain the wave power for leftand right-hand polarized components (B l = B t1 − i B t2 and B r = B t1 + i B t2 ) (Volwerk et al, 2008). Figure 5 presents the wavelet spectrograms for Cluster 3 during the interval of 17:00-17:48 UT.…”
Section: Discussionmentioning
confidence: 99%